Hubungan Iklim Keselamatan Terhadap Perilaku Keselamatan di PT X - Shidqi Cikal Herlambang (2021)
One of the biggest causes of work accidents is unsafe behavior at work. To prevent work accidents, safe behavior is needed. The factor that can affect safety behavior is the safety climate. This study aimed to examine the relationship between safety climate and worker safety behavior. This research used cross sectional design and uses chi-square statistical test. The number of samples was 47 people taken with a total sampling method. The results showed that the frequency of respondents who behaved safely was 53.2%. In the bivariate analysis, there was a relationship between the dimensions of priority, commitment and safety management competence (p = 0.006), management safety empowerment (p = 0.007), the dimensions of safety management justice (p = 0.009), the dimensions of safety commitment (p = 0.031), safety priority and risk acceptance of workers (p = 0.008), dimensions of safety communication, learning, and trust in coworkers (p = 0.003), and dimensions of trust in the effectiveness of the safety system (p = 0.005) on worker safety behavior. All dimensions of safety climate are important factors in shaping safety behavior in the workplace. In particular, management as a source of information related to safety in the workplace plays a role in shaping the perception of workers to increase awareness and shape safe behavior at work. Management is expected to be committed to prioritizing safety compared to production by conducting routine inspections and taking strict action against violations related to safety through clear regulations, management is expected to increase worker awareness regarding risks in the workplace through safety training, regular meeting activities to discuss safety issues, as well as coordinating with production units to commit to improving the safety system in the workplace.